Analysis of Limb Muscle Strength on Accuracy of Shooting Futsal Ball SMA Negeri 2 Martapura Banjar Regency - Windi Yanur; Arifin, Ramadhan; Mulhim (JOURNAL RESPECS (Research Physical Education and Sports), 2024)
Futsal is favored by various groups, ranging from children to adults, many places organize futsal competitions, ranging from students to students and between clubs. Futsal is a sport that is played by every player and requires physical condition. The purpose of this study is to obtain percentage data about the relationship between leg muscle strength and the accuracy of shooting the ball. This study uses descriptive statistical methods. The population of this study were SMA Negeri 2 Martapura futsal players, Banjar Regency with a sample of 30 players. Descriptive statistics describe the percentage data on each variable consisting of the lowest, highest, mean, and standard deviation values. This research instrument uses 2 tests, namely the leg dynamometer test and targeted goal, where the leg dynamometer test (measuring leg muscle strength) shows that in the test results there are 3 students who have very good criteria, namely 10%, 9 students 30% good criteria, 13 students 43% medium criteria, 3 students 10% sufficient criteria, and 2 students very poor criteria less than 7%. While the targeted goal test (measuring the accuracy of shooting the ball) shows that in the test results, there are 6 students who have very good criteria, namely 27%, 8 students with good criteria 27%, 13 students with moderate criteria 43%, 3 students with sufficient criteria 10%, and no students with very poor criteria or 0%.